Borderline personality disorder and the ethics of risk management: The action/consequence model - Warrender, Dan (Nursing ethics, 2018)
Patients with borderline personality disorder are frequent users of inpatient mental health units, with inpatient crisis intervention often used based on the risk of suicide. However, this can present an ethical dilemma for nursing and medical staff, with these clinician responses shifting between the moral principles of beneficence and non-maleficence, dependent on the outcomes of the actions of containing or tolerating risk. This article examines the use of crisis intervention through moral duties, intentions and consequences, culminating in an action/consequence model of risk management, used to explore potential outcomes. This model may be useful in measuring adherence and violation of the principles of beneficence and non-maleficence and therefore an aid to clinical decision making.